2000
DOI: 10.1002/1097-0339(200009)23:3<161::aid-dc4>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic findings in cervical smears in patients using intramuscular medroxyprogesterone acetate (Depo-Provera) for contraception

Abstract: The purpose of the present study was to assess the findings in cervical smears associated with intramuscular depot medroxyprogesterone acetate (Depo‐Provera) contraception. Seventy‐four cervical smears of reproductive‐age patients on Depo‐Provera were reviewed for cytologic abnormalities, predominant cell type, and intermediate cell glycogenation (extensive (EGly) = navicular cells / glycogenation in 10 or more high‐powered fields (hpf); moderate (MGly) = 5–10 hpf; and focal (FGly) = less than 5 hpf). A contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A high ASC rate has been reported from postmenopausal women on hormone replacement and in premenopausal women who are pregnant, lactating, or receiving extrinsic hormones 21–24. It is probable that many of these are over interpreted as they have negative biopsy outcomes and the nuclear changes usually revert back once the hormonal balance is restored.…”
Section: Discussionmentioning
confidence: 99%
“…A high ASC rate has been reported from postmenopausal women on hormone replacement and in premenopausal women who are pregnant, lactating, or receiving extrinsic hormones 21–24. It is probable that many of these are over interpreted as they have negative biopsy outcomes and the nuclear changes usually revert back once the hormonal balance is restored.…”
Section: Discussionmentioning
confidence: 99%
“…Volk et al30 reported that there was extensive glycogenation of intermediate cells in premenopausal women who are pregnant or receiving intramuscular medroxyprogesterone acetate. Although they did not report on the Pap smear technique employed, they did note a much higher rate of ASCUS cytology than in the control women who did not receive replacement hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%